Weevils (Coleoptera, Curculionoidea) of the State National Natural Park "Ulytau" and adjacent territories, Kazakhstan. Report 1. - Izbasar I. Temreshev (Acta Biologica Sibirica, 2024)
The results of primary studies of the fauna of weevils (Coleoptera, Curculionoidea) in the "Ulytau" State National Natural Park and in adjacent territories are presented. In total, 54 species, 40 genera and four families of weevil beetles are recorded, including 2 species Anthribidae, 3 species Attelabidae, 10 species Brentidae and 39 species Curculionidae. In the territory of the National park, 53 species of weevils belonging to 41 genera from 4 families (Anthribidae, Attelabidae, Brentidae and Curculionidae) are recorded. For the adjacent territories, 39 species of weevils belonging to 30 genera from 3 families (Anthribidae, Brentidae and Curculionidae) are recorded. Dryophthorus corticalis (Paykull, 1792) is firstly recorded from Kazakhstan. The distribution in Kazakstan of several other species of weevils (Platystomos albinus (Fabricius, 1758), Perapion affine (Kirby, 1808), Allomalia quadrivirgata (Costa, 1863), Eremoxenus chan Semenow-Tian-Schanskij, 1892, Polydrusus piliferus Hochhuth, 1847, Orchestes alni (Linnaeus, 1758), are Orchestes jota Fabricius, 1787) are clarified.